Are the Non-Monetary Costs of Energy Efficiency Investments Large? Understanding Low Take-up of a Free Energy Efficiency Program - Fowlie, Meredith; Greenstone, Michael; Wolfram, Catherine (American Economic Review, 2015)
We document very low take-up of an energy efficiency program that is widely believed to be privately beneficial. Program participants receive a substantial home “weatherization” retrofit; all installation and equipment costs are covered by the program. Less than 1 percent of presumptively eligible households take up the program in the control group. This rate increased only modestly after we took extraordinary efforts to inform households—via multiple channels–about the sizable benefits and zero monetary costs. These findings are consistent with high non-monetary costs associated with program participation and/or energy efficiency investments.